The Belt and Road Initiative (BRI) Project Implementation in Education Sector: Indonesian Case - Romadhoni, Mohammad; Octastefani, Theresia; Mustofa, Mustofa; Yen, Ai-Chun (Journal of Governance, 2024)
Indonesia and China continue to develop their cooperation, especially through the BRI project. This project aims to strengthen people-to-people bonds and is considered a soft power diplomacy strategy. It includes cultural and educational exchange programs that are popular among students worldwide, including those from Indonesia. Through literature studies, it has been found that many Indonesian students and Santri view this cooperation positively, and it has changed their negative perception of China. One of Indonesia’s largest Islamic organizations, Nahdlatul Ulama (NU), closely cooperates with China in the education sector. However, they do not link this cooperation with the issue of discrimination against the Uyghur people in China. On the other hand, many Kiai from NU have different perspectives on the BRI project, particularly concerning China’s ideology and Indonesia’s history of communism. This paper aims to comprehensively explain the implementation of the BRI project in the education sector and the views of Indonesian students, Santri, and Kiai as representatives of Indonesia’s educational image worldwide.